PENGARUH PENAMBAHAN MAGNESIUM STEARAT DAN JENIS PROTEIN PADA PEMBUATAN BIODEGRADABLE FOAM DENGAN METODE BAKING PROCESS - hendrawati, Nanik; Sofiana, Anna Rubi; Widyantini, Ilmi Nur (Semarang State University, 2015)
Biodegradable foam with cassava starch, protein and chitosan as the basic ingredients can be produced by using baking process method. Variation on magnesium stearate amount and protein types gave different effect on the biodegradable foam quality. The amount of magnesium stearate was varied as 1; 1.6; 2.2; 2.8; 3.4 and 4 % w/w and the sources of protein used in this research were taken from soy bean, peanut and egg white. The foam produced in this research was then tested for its mechanical properties, water resistance and biodegradability. It was found that addition of magnesium stearate as much as 4% w/w reduced water adsorption and biodegradability of foam. Magnesium stearate affected the ability of absorption of water and foam degradation, but did not influence on tensile strength. Different types of protein also gave influence on water absorption, biodegradability and tensile strength. The best improvement of tensile strenght among the compounds tested was shown by soy bean based foam.